Potentials of Endophytic Fungus Untapped, including Novel Bioactive Compounds - Basappa, Kavya Shree; Raghava, Sri; Umesha, Sharan (Pharmacognosy Communications)
Endophytic fungi have attracted a lot of attention over the past century because of their capacity to produce novel bioactive chemicals with a variety of biological properties, which are then used for medical, pharmacological, and agricultural purposes. Endophytic fungi maintain the physiological and ecological characteristics of the host plant by living inside the plant tissues without causing any disease symptoms. Innovative lead chemicals created by endophytic fungus, such paclitaxel and penicillin, cleared the path for the investigation of new bioactive compounds for industrial application. These bioactive substances are classified as alkaloids, peptides, steroids, terpenoids, phenols, quinones, phenols, and flavonoids, among other structural groupings. The current review is concerned with the importance of endophytic fungi in creating novel bioactive substances with a range of biological properties, such as antibacterial, antiviral, antifungal, antiprotozoal, antiparasitic, antioxidant, immunosuppressive, and anticancer effects. The antibacterial and antiviral properties of endophyte-produced metabolites against human infections are highlighted in this review. It also emphasizes how important it is to use these substances as possible cures for major, life-threatening infectious diseases. The need to intensify the search for new, more effective and affordable antimicrobial medications is motivated by the fact that various results have suggested that these bioactive chemicals may considerably contribute to the fight against resistant human and plant infections.
Keywords: Endophytic fungi; Paclitaxel; Penicillin; Bioactive compounds; Antimicrobial drugs